2016
DOI: 10.18276/cej.2016.3-10
|View full text |Cite
|
Sign up to set email alerts
|

Age Differences in Psychoactive Substance Abuse in Population of the Republic of Belarus

Abstract: Background. The recent epidemiological studies conducted in Belarus point to a fall in the average age of registered drug abusers and in the age of drug use onset, an increasing proportion of injecting drugs, and addicted persons. The aim of the study was to evaluate the age differences in the prevalence of psychoactive substance abuse in the Republic of Belarus using the official data of the Ministry of Health. Material and methods. The data on registered drug abusers, who were recorded in the Narcological Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Studies have shown that females are more sensitive than males to physical and psychological effects of drugs (Anker and Carroll, 2011 ; Simmler et al, 2011 ) and present more severe negative drug-related problems related to ecstasy (Allott and Redman, 2007 ), ketamine (Li et al, 2017 ), methamphetamine (Kogachi et al, 2017 ), and other substance use (Fattore et al, 2009 ; van der Plas et al, 2009 ), indicating the importance of understanding sex differences to better guide drug investigation and clinical treatment. In Belarus, compared with people over 30 years old, young drug users under 30 years old had a higher prevalence of the use of hallucinogens and amphetamine-type stimulants (Lelevich et al, 2016 ), and the rates of substance use disorder are highest in individuals younger than 30 years, for both the cocaine users and hallucinogen users (American Psychiatric, 2013 ). Besides, illicit drugs are expensive, thus socioeconomic factors are germane to drug abuse, affecting the accessibility to drugs.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that females are more sensitive than males to physical and psychological effects of drugs (Anker and Carroll, 2011 ; Simmler et al, 2011 ) and present more severe negative drug-related problems related to ecstasy (Allott and Redman, 2007 ), ketamine (Li et al, 2017 ), methamphetamine (Kogachi et al, 2017 ), and other substance use (Fattore et al, 2009 ; van der Plas et al, 2009 ), indicating the importance of understanding sex differences to better guide drug investigation and clinical treatment. In Belarus, compared with people over 30 years old, young drug users under 30 years old had a higher prevalence of the use of hallucinogens and amphetamine-type stimulants (Lelevich et al, 2016 ), and the rates of substance use disorder are highest in individuals younger than 30 years, for both the cocaine users and hallucinogen users (American Psychiatric, 2013 ). Besides, illicit drugs are expensive, thus socioeconomic factors are germane to drug abuse, affecting the accessibility to drugs.…”
Section: Introductionmentioning
confidence: 99%